Average current-mode control of DC-DC power converters - Kazimierczuk, Marian K.; Saini, Dalvir K.; Ayachit, Agasthya (Wiley, 2022)
"The book is aimed at the development of small-signal models and transfer functions related to the inner current and outer voltage loops. Then, the inner loop with average current-mode control is analysed and the dynamic characteristic will be determined for the benefit of power supply designers. First a solid understanding will be established for average current-mode control of basic power converter topologies such as buck, boost, and buck-boost converters in continuous-conduction mode (CCM). Subsequently, more advanced converters such as fly back, impedance-source, and dual-SEPIC (or zeta) converters will be considered."- Resumé vydavatel
Keywords: elektrická regulační technika; měniče (elektrotechnika); electric controllers; electric current converters; elektronické knihy; monografie; electronic books; monographs